Exploring Socioscientific Issues Through a Lens of Reciprocity - Owens, David; Cobbs, Georgia A; Kirk, Eric A (Innovations in Science Teacher Education, 2025)
High-quality elementary science instruction is crucial for laying a solid foundation for young learners while fostering an informed and responsible citizenry. Although contemporary science education has been effective at engaging students in science practice through the exploration of natural phenomena, aiding teachers in designing experiences that prepare students to tackle real-world issues as informed citizens has been more challenging. More specifically, teachers frequently feel unprepared to guide students through diverse perspectives and to incorporate indigenous knowledge into their teaching. To address this gap, the preparation of science educators must include enhancing teachers' abilities to prepare students for future challenges by integrating science with societal issues and employing multiple knowledge systems (beyond Western science) to make sense of and response to such issues. This article describes interdisciplinary 5E instruction about catch limits and overfishing that aims to develop pre-service teachers’ fluency with recognizing the socioscientific nature of contemporary issues through a fishing activity and blending scientific knowledge with other Native perspectives, such as reciprocity, through their analysis of children’s literature. We expect that recognizing the socioscientific nature of contemporary issues and considering them through a lens of reciprocity to promote more just understandings of and responses to SSI.